2012
DOI: 10.1002/ana.23677
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory prostaglandin E2 signaling in a mouse model of Alzheimer disease

Abstract: Objective There is significant evidence for a central role of inflammation in the development of Alzheimer’s disease (AD). Epidemiological studies indicate that chronic use of non-steroidal anti-inflammatory drugs (NSAIDs) reduces the risk of developing AD in healthy aging populations. As NSAIDs inhibit the enzymatic activity of the inflammatory cyclooxygenases COX-1 and COX-2, these findings suggest that downstream prostaglandin signaling pathways function in the pre-clinical development of AD. Here, we inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
69
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(74 citation statements)
references
References 51 publications
4
69
0
Order By: Relevance
“…We then assessed effects of microglial Ep2 deletion on synaptic integrity by quantifying levels of candidate synaptic proteins ( Figure 7, B and C). The loss of synaptophysin correlates with progression of cognitive decline in AD development (46); moreover, studies in transgenic mouse AD models have demonstrated that presynaptic proteins are disrupted early during amyloid accumulation (21,47), with loss of postsynaptic markers occurring at more advanced stages of pathology (48). At 8-9 months, we found a decrease in levels of the presynaptic proteins synaptophysin and ed whether microglial Ep2 negatively affects memory function in the setting of Aβ 42 -mediated inflammation.…”
Section: Conditional Deletion Of Microglial Ep2 Prevents a Functionalmentioning
confidence: 58%
See 2 more Smart Citations
“…We then assessed effects of microglial Ep2 deletion on synaptic integrity by quantifying levels of candidate synaptic proteins ( Figure 7, B and C). The loss of synaptophysin correlates with progression of cognitive decline in AD development (46); moreover, studies in transgenic mouse AD models have demonstrated that presynaptic proteins are disrupted early during amyloid accumulation (21,47), with loss of postsynaptic markers occurring at more advanced stages of pathology (48). At 8-9 months, we found a decrease in levels of the presynaptic proteins synaptophysin and ed whether microglial Ep2 negatively affects memory function in the setting of Aβ 42 -mediated inflammation.…”
Section: Conditional Deletion Of Microglial Ep2 Prevents a Functionalmentioning
confidence: 58%
“…In addition, early-stage AD is characterized by increased cerebrospinal fluid levels of PGE 2 (19,20), supporting the hypothesis that inflammatory actions of brain COX/PGE 2 may underlie preclinical development of AD. Consistently, studies in AD model mice demonstrate reduced amyloid pathology with global deletion of individual PGE 2 G protein-coupled receptors (21)(22)(23), and additional studies have shown a suppressive signaling effect of the PGE 2 receptor EP2 on Aβ 42 phagocytosis (24,25). These studies, along with the recent demonstration of a broad regulatory function of EP2 signaling on cell cycle, cytoskeletal, and immune genes in quiescent microglia (26), suggest that microglial EP2 signaling may be a general suppressor of immune and nonimmune processes that protect against onset and progression of AD pathology.…”
Section: Introductionmentioning
confidence: 58%
See 1 more Smart Citation
“…[4][5][6] PGE 2 receptor EP3 (EP3R) is expressed mainly by neurons and activated glial cells in brain 7,8 and is associated with neuronal death. 8,9 Of the four G-proteincoupled PGE 2 receptors, EP3R is unique in its ability to bind to multiple G-proteins based on different spliced carboxy-terminal tail isoforms. 10 Although it signals primarily via Gi/Gs, EP3R can also be linked to the G 12/13 protein, resulting in activation of the small G-protein Rho.…”
Section: Introductionmentioning
confidence: 99%
“…85,[95][96][97] In addition, recent findings in mouse models suggest a role for COX/prostaglandin E 2 signalling in the development of AD. 98 …”
Section: O X I D At I V E S T R E S Smentioning
confidence: 99%